Demand and Supply Curves - Maverick, Lewis A. (Quarterly Journal of Economics, 1940)
Journal Article Demand and Supply Curves Get access Lewis A. Maverick Lewis A. Maverick University of California, Los Angeles Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 54, Issue 2, February 1940, Pages 307–313, https://doi.org/10.2307/1883337 Published: 01 February 1940